Prognostic factor of heart failure in children with left-to-right shunt acyanotic congenital heart disease - Weny Inrianto; Indah K. Murni; Sri Mulatsih; Sasmito Nugroho (Paediatrica Indonesiana, 2019)
Background Anemia is highly prevalent and affects morbidity and mortality in adults with acquired heart disease. However, its role in children with acyanotic congenital heart disease (CHD) is unclear. Objective To assess anemia and other potential prognostic factors of congestive failure in children with left-to-right shunt acyanotic CHD. Methods We conducted a case-control study in the Pediatric Cardiology Clinic, Dr. Sardjito Hospital from January to December 2017 in children with left-to-right shunt acyanotic CHD. The case and control groups consisted of subjects with and without heart failure, respectively. Anemia was defined as hemoglobin concentration <11 g/dL. Measured outcome was the prevalence of congestive heart failure, as determined by the Ross criteria. Anemia, defect type, defect size, age at diagnosis, and gender were analyzed by logistic regression analysis as potential predictive factors of heart failure. Results Of 100 children with left-to-right shunt acyanotic CHD, 50 had heart failure (the case group) and 50 did not (the control group). The prevalence of anemia was 45%. Multivariable logistic regression revealed that defect size was the most significant factor for predicting heart failure, with adjusted OR 7.6 (95%CI 2.5 to 22.8) for moderate shunts and 21.1 (95%CI 6.8 to 65.4) for large shunts. Anemia, type of defect, age of diagnosis, and gender were not statistically significant factors for predicting outcomes. Conclusion Anemia is not a significant, prognostic factor for heart failure in children with left-to-right shunt acyanotic CHD. However, moderate and large shunts in children with left-to-right shunt acyanotic CHD are predictive of the occurrence of congestive heart failure.